Nilai Tukar Rupiah dan Tingkat Inflasi terhadap Penerimaan Pajak Penghasilan - Lathifa Gita Pratiwi; Diamonalisa Sofianty; Asri Suangga (Bandung Conference Series: Accountancy, 2024)
Abstract. Income tax is one of the sources of state income with the largest amount every year. The existence of macro aspect phenomena, especially the Rupiah Exchange Rate and the Inflation Rate, has resulted in a decline in income tax revenues. The research was conducted with the aim of examining the Rupiah Exchange Rate, Inflation Rate and Income Tax Revenue in Indonesia for the period 1993-2023. This research uses a descriptive verification method, a quantitative approach using multiple linear regression analysis techniques using Eviews 12. The population in this research consists of the Rupiah Exchange Rate, Inflation Rate and Income Tax Receipts. A purposive sampling technique was used in the research with a sample of 31 consisting of the Rupiah Exchange Rate for the 1993-2023 period, the Inflation Rate for the 1993-2023 period, and Income Tax Revenue for the 1993-2023 period. The research data is in the form of secondary data with documentation data collection techniques through the official websites of the Badan Pusat Statistik (BPS), Bank Indonesia (BI), and the Ministry of Finance. The test results in the research prove (1) The Rupiah Exchange Rate has a significant positive influence on Income Tax Revenues during the 1993-2023 period. (2) The inflation rate has a significant negative influence on income tax revenues during the 1993-2023 period. Abstrak. Pajak penghasilan menjadi salah satu sumber pemasukan negara dengan jumlah terbesar setiap tahunnya. Adanya fenomena aspek makro terutama Nilai Tukar Rupiah dan Tingkat Inflasi mengakibatkan turunnya penerimaan pajak penghasilan. Penelitian dilakukan dengan tujuan untuk menguji Nilai Tukar Rupiah, Tingkat Inflasi, dan Penerimaan Pajak Penghasilan di Indonesia periode 1993-2023. Penelitian ini menggunakan metode deskriptif verifikatif pendekatan kuantitatif dengan menggunakan teknik analisis regresi linier berganda menggunakan Eviews 12. Populasi dalam penelitian ini terdiri dari Nilai Tukar Rupiah, Tingkat Inflasi, dan Penerimaan Pajak Penghasilan. Teknik sampling purposif digunakan dalam penelitian dengan sampel sebanyak 31 terdiri dari Nilai Tukar Rupiah periode 1993-2023, Tingkat Inflasi periode 1993-2023, dan Penerimaan Pajak Penghasilan periode 1993-2023. Data penelitian berupa data sekunder dengan teknik pengumpulan data dokumentasi melalui situs resmi Badan Pusat Statistik (BPS), Bank Indonesia (BI), dan Kementerian Keuangan. Hasil uji dalam penelitian membuktikan (1) Nilai Tukar Rupiah memberikan pengaruh signifikan positif terhadap Penerimaan Pajak Penghasilan selama periode 1993-2023. (2) Tingkat Inflasi memberikan pengaruh signifikan negatif terhadap Penerimaan Pajak Penghasilan selama periode 1993-2023.